2011
DOI: 10.1016/j.jacc.2010.05.071
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics, Management, and Outcomes of Patients Diagnosed With Acute Pulmonary Embolism in the Emergency Department

Abstract: Patients diagnosed with acute PE in U.S. EDs have high functional status, and their mortality rate is low. These registry data suggest that appropriate initial medical management of ED patients with severe PE with anticoagulation is poorly standardized and indicate a need for research to determine the appropriate threshold for empiric treatment when PE is suspected before diagnostic confirmation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

25
299
8
40

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 490 publications
(372 citation statements)
references
References 25 publications
25
299
8
40
Order By: Relevance
“…En un 90% de los casos la sospecha de TEP se plantea en base a signos clínicos 8 , junto a la presencia de factores de riesgo, presentes en el 75%-94% de los casos 9,10 . El TEP se puede presentar con un amplio espectro clínico, desde apenas sínto-mas hasta shock o inestabilidad hemodiná-mica, variables en función de la gravedad 11 . Los síntomas más habituales son disnea, que puede ser de reposo o de esfuerzo, y dolor torácico de características pleuríti-cas.…”
Section: Tromboembolismo Pulmonarunclassified
“…En un 90% de los casos la sospecha de TEP se plantea en base a signos clínicos 8 , junto a la presencia de factores de riesgo, presentes en el 75%-94% de los casos 9,10 . El TEP se puede presentar con un amplio espectro clínico, desde apenas sínto-mas hasta shock o inestabilidad hemodiná-mica, variables en función de la gravedad 11 . Los síntomas más habituales son disnea, que puede ser de reposo o de esfuerzo, y dolor torácico de características pleuríti-cas.…”
Section: Tromboembolismo Pulmonarunclassified
“…All but one of the phase III studies with the new oral agents included both patients with deep vein thrombosis and patients with pulmonary embolism. The risk of early in-hospital death in patients with pulmonary embolism ranges from 1% to >30%, depending on clinical presentation, and is higher than in patients with deep vein thrombosis [4][5][6]. This requires the availability of efficacy and safety data for the new oral agents across the spectrum of severity of pulmonary embolism.…”
Section: Introductionmentioning
confidence: 99%
“…The annual incidence is approximately 1-3 per 1000 adults in developed countries [2]. Recent studies such as COPER and EMPEROR have shown that some important prognostic risk factors associated with death from pulmonary embolism (17 %) were age (over 70 years), cancer, congestive heart failures, chronic obstructive pulmonary disease, systemic arterial hypotension, tachypnea and the mortality rate directly attributable to pulmonary embolism was only 1 % [3,4]. These prognostic risk factors are often used to identify provoked VTE [5].…”
Section: Introductionmentioning
confidence: 99%